Robots in K-12 education a new technology for learning - Barker, Bradley S.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book explores the theory and practice of educational robotics in the K-12 formal and informal educational settings, providing empirical research supporting the use of robotics for STEM learning"--Provided by publisher.
1. Educational Robotics Theories and Practice: Tips for how to do it Right / Amy Eguchi -- 2. Designing evaluations for K-12 robotics education programs / Kristen Stubbs, Jennifer Casper, and Holly A. Yanco -- 3. Generating transferable skills in STEM through educational robotics / Carl A. Nelson -- 4. In and out of the school activities implementing IBSE and constructionist learning methodologies by means of robotics / G. Barbara Demo ... [et al.] -- 5. Robotics and problem-based learning in STEM formal educational environments / Neal Grandgenett ... [et al.] -- 6. Medical robotics in K-12 education Ronald Rockland ... [et al.] -- 7. Robots underwater! Learning science, engineering and 21st century skills: the evolution of curricula, professional development and research in formal and informal contexts / Elisabeth McGrath ... [et al.] -- 8. Programming robots in kindergarten to express identity: an ethnographic analysis / Marina U. Bers, and Alyssa B. Ettinger -- 9. The impact of educational robotics on student STEM learning, attitudes, and workplace skills / Gwen Nugent, Bradley S. Barker, and Neal Grandgenett -- 10. The mediating role of context in an urban after-school robotics program: using activity systems to analyze and design robust STEM learning environments / John Y. Baker -- 11. Building technical knowledge and engagement in robotics: an examination of two out-of-school programs / Kimberley Gomez ... [et al.] -- 12. STEM outreach with the Boe-Bot / Ronda K. Cole -- 13. Developing and evaluating a web-based, multi-platform curriculum for after-school robotics / Fred G. Martin ... [et al.] -- 14. Learning geospatial concepts as part of a non-formal education robotics experience / Viacheslav Adamchuk ... [et al.] -- 15. From grade school to grad school: an integrated STEM pipeline model through robotics / Ross A. Mead, Susan L. Thomas, and Jerry B. Weinberg -- 16. Promoting diversity and public school success in robotics competitions / Jeffrey Rosen, Fred Stillwell, and Marion Usselman -- 17. Educational robotics and broadening participation in STEM for underrepresented student groups / Stephanie Ludi.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 2/21/2012).
Keywords: Robotics -- Study and teaching -- United States; Science -- Study and teaching -- United States; Engineering -- Study and teaching -- United States; Technical education -- Study and teaching -- United States; Constructionist learning methodologies; Educational robotics; Hardware and software for robotics; Innovation in formal and informal educational environments; Medibotics; Project-based learning with robotics; Robotics competitions; Robotics outreach programs; Theories for educational robotics; Virtual robotics; Electronic books